Quantum dot and perovskite two-end laminated solar cell and preparation method thereof
By adopting the PbS quantum dot and perovskite two-end stacking structure in perovskite-crystalline silicon stacked solar cells, the problems of weak absorption capacity and high production cost of crystalline silicon materials are solved, and efficient photoelectric conversion and stable battery performance are achieved.
Patent Information
- Application Number
- CN202411993142.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
Among the existing perovskite-crystalline silicon stacked solar cells, as the base battery material, crystalline silicon has problems such as weak ability to absorb sunlight, high cost, large energy consumption in production processes, and environmental pollution, which limits its feasibility in large-scale applications.
PbS quantum dots are used as the absorbent material for the bottom battery of the stacked battery, and a perovskite absorbent layer is used as the absorbent material for the top battery to build a stacked structure at both ends of the quantum dots and perovskites. By regulating the size of the quantum dots, their band gaps are adjusted to achieve effective absorption of the solar spectrum and photoelectric conversion.
It significantly improves the photoelectric conversion efficiency of solar cells, reduces production costs, reduces energy consumption, and improves the stability and life of the battery.
Smart Images

Figure CN119767926A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a quantum dot and perovskite two-terminal stacked solar cell and a preparation method thereof. Background Art
[0002] In recent years, with the growing global demand for renewable energy and increasing awareness of environmental protection, perovskite-based tandem solar cells have become a hot topic in the research field due to their potential high theoretical efficiency limit. This type of cell achieves effective absorption and conversion of a wider range of the solar spectrum by combining semiconductor materials with different band gaps, thereby significantly improving the photoelectric conversion efficiency.
[0003] Among the many tandem cell systems, significant progress has been made in perovskite-crystalline silicon tandem solar cells, perovskite-perovskite tandem solar cells, and perovskite-CIGS (copper indium gallium selenide) tandem solar cells. These tandem cells optimize the band gap of each layer of material so that sunlight is effectively absorbed in different layers, thereby achieving higher energy conversion efficiency.
[0004] Theoretical calculations and predictions show that for a two-terminal tandem cell, when the band gap of the light-absorbing layer material of the top cell is about 1.7eV and the band gap of the light-absorbing layer material of the bottom cell is about 1.1eV, the theoretical limit efficiency of the tandem cell can be as high as 46%. This efficiency is much higher than the theoretical limit efficiency of silicon-based single-junction solar cells and perovskite single-junction solar cells, demonstrating the great potential of tandem cells in improving photoelectric conversion efficiency.
[0005] However, although the research on perovskite-crystalline silicon tandem solar cells under this bandgap combination is relatively thorough, there are still some challenges for crystalline silicon as a bottom cell material. Crystalline silicon is an indirect bandgap semiconductor, which means that its ability to absorb sunlight is relatively weak and requires a thicker material layer (usually up to hundreds of microns) to effectively absorb sunlight. This not only increases the cost of the material, but also makes the energy consumption in the production process higher. In addition, the preparation process of crystalline silicon is relatively complicated, and environmental pollution may occur during the production process, which further limits its feasibility in large-scale applications. Summary of the invention
[0006] The purpose of the present invention is to solve the technical problems in the prior art and to provide a quantum dot and perovskite two-terminal stacked solar cell and a preparation method thereof, which can not only improve the photoelectric conversion efficiency of the solar cell but also reduce the cost.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: In the first aspect, the present invention provides a quantum dot and perovskite two-terminal stacked solar cell, which includes, from bottom to top, a transparent conductive glass substrate, a first hole transport layer, a perovskite light absorption layer, a first electron transport layer, a transparent electrode layer, a second hole transport layer, a PbS quantum dot light absorption layer, a second electron transport layer and a top electrode.
[0008] Preferably, the transparent conductive glass substrate comprises transparent glass and a transparent electrode FTO arranged on the surface thereof.
[0009] Preferably, the material of the hole transport layer is NiO x ,CuSCN,CuO x or CuI.
[0010] Preferably, the perovskite light absorbing layer is a three-dimensional CsPbBr x I 3-x structure.
[0011] Preferably, the material of the electron transport layer is TiO2, SnO2, fullerene or a fullerene derivative.
[0012] Preferably, the fullerene derivative is PCBM.
[0013] Preferably, the material of the top electrode is gold, silver, copper, graphite or amorphous carbon.
[0014] Preferably, the thickness of the perovskite light absorbing layer is 300-500 nm.
[0015] Preferably, the thickness of the PbS quantum dot light-absorbing layer is 100-200 nm.
[0016] In a second aspect, the present invention provides a method for preparing a quantum dot and perovskite two-terminal stacked solar cell, which specifically comprises the following steps: A first hole transport layer, a perovskite light absorbing layer and an electron transport layer are sequentially deposited on a transparent conductive glass substrate; a transparent electrode layer is placed on the first electron transport layer, and a second hole transport layer, a PbS quantum dot light absorbing layer, a second electron transport layer and a top electrode are sequentially deposited on the transparent electrode layer.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention can effectively absorb sunlight by using PbS quantum dots as the light-absorbing material of the bottom cell of the tandem battery; and can absorb wide-wavelength sunlight and convert it into electrical energy by using the perovskite light-absorbing layer as the light-absorbing material of the top cell of the tandem battery. By using PbS quantum dots and perovskites in synergy, a two-terminal tandem battery structure is realized. In addition, the band gap of the PbS quantum dots can be regulated by the size of the quantum dots, and the size of the quantum dots can be adjusted to adjust the band gap to the ideal value of theoretical calculation, thereby achieving a huge improvement in the photoelectric conversion efficiency.
[0018] Furthermore, the thickness of the perovskite light-absorbing layer is 300-500 nm, which not only ensures sufficient light absorption but also avoids the difficulty of charge transfer caused by excessive thickness, optimizes the overall structure of the battery, and improves the stability and life of the battery.
[0019] Furthermore, the thickness of the PbS quantum dot light absorbing layer is 100-200 nm, so that the PbS quantum dot light absorbing layer can fully absorb different wavelength components in sunlight, thereby improving the spectrum utilization rate; at the same time, it has a suitable band gap value, thereby improving the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 This is a schematic diagram of the structure of a quantum dot and perovskite two-terminal stacked solar cell of the present invention; Figure 2 The JV curve of the stacked solar cell prepared in the example.
[0022] Among them: 1-transparent conductive glass substrate; 2-first hole transport layer; 3-perovskite light absorption layer; 4-first electron transport layer; 5-transparent electrode layer; 6-second hole transport layer; 7-PbS quantum dot light absorption layer; 8-second electron transport layer; 9-top electrode. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0024] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0026] In the description of the embodiments of the present invention, it should be noted that if the terms "upper", "lower", "horizontal", "inner", etc. indicate an orientation or positional relationship based on the orientation or positional relationship shown in the drawings, or the orientation or positional relationship in which the product of the invention is usually placed when in use, it is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0027] In addition, if the term "horizontal" appears, it does not mean that the component must be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", which does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0028] In the description of the embodiments of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0029] The present invention is further described in detail below in conjunction with the accompanying drawings: like Figure 1As shown, the first purpose of the present invention is to provide a two-terminal stacked solar cell based on layered two-dimensional materials and three-dimensional perovskites, the light-absorbing material of the top cell (referring to the cell through which light first passes) is a perovskite with a band gap of about 1.7eV, and the light-absorbing material of the bottom cell is a PbS quantum dot with a band gap of about 1.1eV. The cell of the present invention comprises, from bottom to top, a transparent conductive glass substrate 1, a first hole transport layer 2, a perovskite light-absorbing layer 3, a first electron transport layer 4, a transparent electrode layer 5, a second hole transport layer 6, a PbS quantum dot light-absorbing layer 7, a second electron transport layer 8 and a top electrode 9.
[0030] The transparent conductive glass substrate 1 has excellent transparency and conductivity, and can realize the functions of transparency and conductivity at the same time. The high transmittance can convert more solar energy into electrical energy and improve the efficiency of the photovoltaic power generation system. Among them, the transparent conductive glass substrate 1 includes transparent glass and a transparent electrode FTO coated on its surface. Fluorine-doped SnO2 conductive glass (SnO2: F, referred to as FTO) is an n-type semiconductor material, which is prepared by doping fluorine into tin oxide (SnO2). This doping process changes the electronic structure of tin oxide, making it more conductive while maintaining good transparency. The crystal structure of FTO maintains the tetragonal system of SnO2. Fluorine doping mainly replaces oxygen atoms in the lattice to provide additional free carriers (electrons), thereby improving the conductivity of the material; FTO has the characteristics of high transmittance (up to more than 90%) and high conductivity, which makes it have broad application prospects in the fields of solar cells, touch screens and architectural glass.
[0031] The material of the first hole transport layer 2 is NiO x ,CuSCN,CuO x Or CuI, preferably CuSCN. Its thickness is 20-60nm, which can promote the transmission of photogenerated holes from the perovskite layer to the bottom electrode, while blocking the reverse flow of electrons, reducing charge recombination and improving photoelectric conversion efficiency. NiO x (Nickel Oxide) is a transition metal oxide with excellent electrical properties and chemical stability. x The film has good light transmittance, which allows more sunlight to penetrate into the interior of the solar cell, be captured by the light absorption layer and converted into electrical energy. At the same time, it has good chemical stability in the air and is not easily oxidized or reduced, thus ensuring the performance stability of solar cells during long-term use. CuSCN (cuprous thiocyanate) is a hole transport layer material with low defect density, high hole mobility and low cost. It can effectively transport holes and reduce the loss of holes during the transmission process, thereby improving the photoelectric conversion efficiency of solar cells. Compared with traditional hole transport layer materials, CuSCN has a lower cost, which is conducive to reducing the production cost of solar cells. CuO x(Copper Oxide) is a common inorganic compound with various valence states and crystal structures. CuO x The energy band structure of CuI can be regulated by adjusting its preparation process and doping elements to better match it with other layer materials of solar cells. At the same time, due to its good conductivity, it can effectively transport holes and reduce the loss of charge during the transmission process. CuI has excellent photoelectric properties and can effectively absorb and convert light energy, thereby improving the photoelectric conversion efficiency of solar cells. In addition, CuI can also be compounded with other materials (such as perovskite materials) to form a composite hole transport layer, further improving the photoelectric conversion efficiency and stability of solar cells.
[0032] The perovskite light absorbing layer 3 is a three-dimensional CsPbBr x I 3-x The structure can adjust the band gap of the perovskite material by adjusting the ratio of Br and I, thereby optimizing its photoelectric performance. The thickness of the perovskite light-absorbing layer 3 in the present invention is 300-500nm, which is conducive to the absorption of photons and the transmission of carriers, ensuring sufficient light absorption and avoiding the difficulty of charge transmission caused by excessive thickness, optimizing the overall structure of the battery, and improving the stability and life of the battery. Secondly, the perovskite material has a high absorption coefficient, and the thickness of 300-500nm is sufficient to absorb most of the sunlight, especially visible light and near-infrared light, thereby improving the photoelectric conversion efficiency of the solar cell. The band gap of the perovskite light-absorbing layer 3 is about 1.7eV, which can meet the preferred band gap range of the light-absorbing layer material of the top cell of the stacked cell and improve the photoelectric conversion efficiency. The perovskite layer can absorb sunlight of a wide wavelength and convert it into electrical energy; it has excellent photoelectric properties and a tunable band gap, and can effectively absorb sunlight and generate electron-hole pairs.
[0033] The material of the first electron transport layer 4 is TiO2, SnO2, fullerene or fullerene derivative (preferably fullerene), and its thickness is 20~60nm. The thickness range of 20~60nm helps to balance the relationship between electron transport and battery stability. An overly thick electron transport layer will increase the internal resistance of the battery and reduce the photoelectric conversion efficiency; while an overly thin electron transport layer cannot provide sufficient electron channels, resulting in poor charge transfer. The first electron transport layer 4 can reduce the energy barrier between the electrode and the perovskite, promote the extraction and transfer of charges; at the same time, it can effectively block holes, inhibit carrier recombination, and improve the photoelectric conversion efficiency and stability of the battery. The TiO2 electron transport layer has a low resistivity, which can reduce the interface resistance inside the perovskite battery and improve the overall current output capacity of the battery. SnO2 is an n-type oxide semiconductor material with high conductivity and can effectively transport electrons. Fullerene and its derivatives have excellent electron mobility, can quickly transport electrons, and reduce the recombination and loss of electrons during the transmission process.
[0034] The transparent electrode layer 5 is prepared by ALD deposition as an intermediate layer, and can provide a transparent conductive function to support the charge transfer and light absorption of the upper structure, thereby helping to improve the overall photoelectric conversion efficiency.
[0035] The material of the second hole transport layer 6 is NiO x ,CuSCN,CuO x Or CuI, with a thickness of 20-60 nm. The second hole transport layer 6 can be optimized for the PbS quantum dot light absorption layer 7 to promote the transmission of photogenerated holes and block electrons, further optimizing the photoelectric conversion efficiency of the solar cell.
[0036] The thickness of the PbS quantum dot light-absorbing layer 7 is 100~200nm. PbS quantum dots are a direct bandgap semiconductor whose bandgap can be controlled by the size of quantum dots. The size of quantum dots can be selected to make its bandgap about 1.1eV, which meets the bandgap requirements of the bottom cell light-absorbing material of the tandem battery, and realizes the effective absorption of the solar spectrum and the maximization of the photoelectric conversion efficiency. In the design of tandem batteries, the performance of the bottom cell has a crucial impact on the overall efficiency. With its tunable bandgap and excellent photoelectric properties, PbS quantum dots have become ideal bottom cell light-absorbing materials. By precisely controlling the size of quantum dots, researchers can optimize the bottom cell's absorption of sunlight and ensure that more photons are effectively converted into current, thereby improving the overall performance of the tandem battery.
[0037] In addition, as part of a planar structure solar cell, the bottom cell based on PbS as the absorption layer has shown significant advantages in the preparation process. As a new type of semiconductor material, PbS has unique electrical and optical properties. As an absorption layer, it can not only effectively absorb sunlight, but also realize high-performance solar cells through a simple preparation process. Compared with traditional crystalline silicon materials, PbS-based solar cells consume less energy during the preparation process, have lower costs, and have less impact on the environment.
[0038] The material of the second electron transport layer 8 is TiO2, SnO2, fullerene or fullerene derivatives (such as PCBM). The second electron transport layer 8 can be optimized for the PbS quantum dot light absorption layer to promote the transmission of electrons and block holes. PCBM is a commonly used organic semiconductor material with a unique electronic structure and photoelectric properties. PCBM has strong electron transport properties. When used as an electron transport layer, it can effectively guide the photogenerated electrons generated by the perovskite layer, reduce the recombination and loss of electrons during the transmission process, and thus improve the photoelectric conversion efficiency of the battery.
[0039] The material of the top electrode 9 is gold, silver, copper, graphite or amorphous carbon (preferably copper), which is used to collect and conduct the current generated by photoelectric conversion to achieve efficient photoelectric conversion. Its thickness is 20~60nm, which can reduce the resistance of the electrode, thereby reducing the internal resistance of the battery or device and improving the output efficiency of the current. Under the premise of ensuring mechanical strength, the electrode with a thickness of 20~60nm is conducive to the transmission of electrons and improves the conductivity, especially in high-frequency or high current density applications.
[0040] Gold, silver and copper all have good electrical conductivity, and high electrical conductivity helps to reduce the internal resistance of the battery and improve the photoelectric conversion efficiency. Compared with gold and silver, copper is cheaper, which helps to reduce the cost of solar cells, and copper also has good electrical conductivity, which can meet the needs of most solar cells. Graphite is an inorganic non-metallic material with good electrical and thermal conductivity, which helps to ensure the stable operation of solar cells. Amorphous carbon is an allotrope of carbon with an amorphous structure, which has a higher specific capacity and better cycle stability. At the same time, the preparation process of amorphous carbon is relatively simple and low cost.
[0041] The second object of the present invention is to provide a method for preparing a quantum dot and perovskite two-terminal stacked solar cell, which specifically comprises the following steps: A first hole transport layer 2, a perovskite light absorbing layer 3 and an electron transport layer 4 are sequentially deposited on a transparent conductive glass substrate 1; a transparent electrode layer 5 is placed on the first electron transport layer 4, and a second hole transport layer 6, a PbS quantum dot light absorbing layer 7, a second electron transport layer 8 and a top electrode 9 are sequentially deposited on the transparent electrode layer 5.
[0042] The preparation method of the present invention realizes wide-range absorption and efficient utilization of the solar spectrum by constructing a two-end stacked structure. The perovskite light absorption layer 3 and the PbS quantum dot light absorption layer 7 are optimized for sunlight of different wavelengths, respectively, so that the stacked battery can capture and convert more light energy, and the layered design reduces the loss of light energy, thereby significantly improving the photoelectric conversion efficiency. In particular, for the two-end stacked battery, when the band gap of the light absorption layer material of the top battery is about 1.7eV and the band gap of the light absorption layer material of the bottom battery is about 1.1eV, the theoretical limit efficiency of the stacked battery can be as high as 46%. This is consistent with the ideal value of the band gap value range of the first perovskite light absorption layer 3 (as the top battery) and the PbS quantum dot light absorption layer 7 (as the bottom battery) in the present invention, and its theoretical limit efficiency can reach 46%, which is much higher than the theoretical limit efficiency of silicon-based single-junction solar cells and perovskite single-junction solar cells, and realizes efficient utilization of energy.
[0043] The two-terminal tandem solar cell of the present invention has the characteristics of high efficiency and stability, and is suitable for a variety of application scenarios. Whether it is a large-scale photovoltaic power station or a distributed photovoltaic power generation system, the tandem battery of the present invention can provide a reliable power supply. In addition, with the further development of technology, the tandem battery of the present invention is also expected to be widely used in portable electronic devices, aerospace and other fields.
[0044] Example A first hole transport layer 2, a perovskite light absorbing layer 3 and an electron transport layer 4 are sequentially deposited on a transparent conductive glass substrate 1; a transparent electrode layer 5 is placed on the first electron transport layer 4, and a second hole transport layer 6, a PbS quantum dot light absorbing layer 7, a second electron transport layer 8 and a top electrode 9 are sequentially deposited on the transparent electrode layer 5 to obtain a stacked solar cell; wherein the transparent electrode layer 5 is prepared by ALD deposition.
[0045] like Figure 2 As shown, the prepared stacked solar cell was tested for performance. Under room temperature, a 3A solar simulator was used to test the performance of the stacked solar cell at 100 mW / cm 2 The conversion efficiency of the stacked cell prepared in the embodiment was tested under light intensity, and the effective area of the cell was 0.084 cm 2 .
[0046] The test results of the stacked solar cell are shown in Table 1: Table 1 Performance data of the laminated solar cell prepared in Example
[0047] It can be concluded that the efficiency of the two-terminal stacked solar cells based on quantum dots and perovskites reaches 30.18%.
[0048] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A quantum dot and perovskite two-terminal stacked solar cell, characterized in that: From bottom to top, it includes a transparent conductive glass substrate (1), a first hole transport layer (2), a perovskite light absorption layer (3), a first electron transport layer (4), a transparent electrode layer (5), a second hole transport layer (6), a PbS quantum dot light absorption layer (7), a second electron transport layer (8) and a top electrode (9).
2. A quantum dot and perovskite two-terminal stacked solar cell according to claim 1, characterized in that: The transparent conductive glass substrate (1) comprises transparent glass and a transparent electrode FTO arranged on the surface thereof.
3. A quantum dot and perovskite two-terminal tandem solar cell according to claim 1, characterized in that: The material of the hole transport layer is NiO x ,CuSCN,CuO x or CuI.
4. A quantum dot and perovskite two-terminal stacked solar cell according to claim 1, characterized in that: The perovskite light absorbing layer (3) is a three-dimensional CsPbBr x I 3-x structure.
5. The quantum dot and perovskite two-terminal stacked solar cell according to claim 1, characterized in that: The material of the electron transport layer is TiO2, SnO2, fullerene or a fullerene derivative.
6. A quantum dot and perovskite two-terminal stacked solar cell according to claim 5, characterized in that: The fullerene derivative is PCBM.
7. The quantum dot and perovskite two-terminal tandem solar cell according to claim 1, characterized in that: The material of the top electrode (9) is gold, silver, copper, graphite or amorphous carbon.
8. The quantum dot and perovskite two-terminal tandem solar cell according to claim 1, characterized in that: The thickness of the perovskite light-absorbing layer (3) is 300-500 nm.
9. The quantum dot and perovskite two-terminal tandem solar cell according to claim 1, characterized in that: The thickness of the PbS quantum dot light absorption layer (7) is 100-200 nm.
10. A method for preparing a quantum dot and perovskite two-terminal stacked solar cell according to any one of claims 1 to 9, characterized in that: The specific steps include: A first hole transport layer (2), a perovskite light absorption layer (3) and an electron transport layer (4) are sequentially deposited on a transparent conductive glass substrate (1); a transparent electrode layer (5) is placed on the first electron transport layer (4); and a second hole transport layer (6), a PbS quantum dot light absorption layer (7), a second electron transport layer (8) and a top electrode (9) are sequentially deposited on the transparent electrode layer (5).